2019
DOI: 10.1038/s41590-019-0539-2
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous oxidized phospholipids reprogram cellular metabolism and boost hyperinflammation

Abstract: Pathogen-associated molecular patterns (PAMPs) have the capacity to couple inflammatory gene expression to changes in macrophage metabolism, both of which influence subsequent inflammatory activities. Similar to their microbial counterparts, several self-encoded damageassociated molecular patterns (DAMPs) induce inflammatory gene expression. However, whether this symmetry in host responses between PAMPs and DAMPs extends to metabolic shifts is unclear. Here we report that the self-encoded oxidized phospholipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(127 citation statements)
references
References 60 publications
3
124
0
Order By: Relevance
“…Namely, in MO-GMCSF cells, we identified strong enrichment of pathways associated with oxidative signaling consistent with emerging models relating metabolism in driving macrophage state (Cameron et al, 2019;West et al, 2011). We speculate that this interplay between oxidative signaling and metabolic state influence a multitude of macrophage functions, such as bacterial clearance and atherosclerosis, in vivo (Di Gioia et al, 2020;Huang et al, 2018;Wang et al, 2020). We identified and validated several novel markers of macrophage state.…”
Section: Gm-csf Mediates a Durable Switch In Il-10 Productionsupporting
confidence: 78%
“…Namely, in MO-GMCSF cells, we identified strong enrichment of pathways associated with oxidative signaling consistent with emerging models relating metabolism in driving macrophage state (Cameron et al, 2019;West et al, 2011). We speculate that this interplay between oxidative signaling and metabolic state influence a multitude of macrophage functions, such as bacterial clearance and atherosclerosis, in vivo (Di Gioia et al, 2020;Huang et al, 2018;Wang et al, 2020). We identified and validated several novel markers of macrophage state.…”
Section: Gm-csf Mediates a Durable Switch In Il-10 Productionsupporting
confidence: 78%
“…However, in cases of tissue injury, reprogrammed leukocytes could funnel energy to drive hyperinflammation. A recent paper by Di Gioia and colleagues showed that oxidized phospholipids derived from 1-palmitoyl-2-arachidonyl-snglycero-3-phosphorylcholine (oxPAPC) can induce increased leukocyte oxidative metabolism and hyperinflammation, especially in the presence of microbial ligands such as LPS (190). Oxidized phospholipids are damage associated molecular patterns (DAMPS) that are released following tissue injury.…”
Section: Metabolic Reprogramming and Innate Immune Memorymentioning
confidence: 99%
“…Oxidized phospholipids are damage associated molecular patterns (DAMPS) that are released following tissue injury. Di Gioia and colleagues reported that oxPAPC and LPS strongly drive production of pro-IL-1β in macrophages, which is cleaved and secreted as the mature protein upon activation of the inflammasome by DAMPS such as ATP (190). However, the ramifications of these alterations in models of acute inflammation remain to be fully elucidated since a study by Chu and colleagues showed that oxPAPC inhibits non-canonical inflammasome activation and is protective in an experimental model of septic shock (191).…”
Section: Metabolic Reprogramming and Innate Immune Memorymentioning
confidence: 99%
“…Oxidized phospholipids (PLs) (oxPL) are recognized as danger-associated molecules and are therefore linked to certain inflammatory pathways. OxPLs derived from PC have been found to induce an Il-1β-driven hyperinflammatory state in macrophages by promoting both OXPHOS and glycolysis; a phenotype also displayed in vivo in hypercholesterolemic mice after LPS administration [97]. OxPL have thus been implicated in steatohepatitis [98], atherosclerosis [99,100] and more recently, in obesity and diet-induced ATM activation [33].…”
Section: Glycerophospholipids (Gpl)mentioning
confidence: 99%